The code-mixing of Chinese-Indonesian-English (Chindolish) at Hang Kesturi School Medan - Frida, Karunia Devi; Lubis, Syahron (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
Indonesia has high linguistic and cultural diversity, where multilingualism is common, especially in the Chinese community. In Medan, the use of mixed language between Chinese (Hokkien), Indonesian, and English, known as Chindolish, is often encountered daily, including in the school environment. At Hang Kesturi School Medan, English teachers usually use Chindolish as a communication strategy to help students understand the subject matter more quickly. This study aims to find out the types of Chindolish code mix used by teachers and the reasons behind its use in the context of language teaching. This study used a qualitative descriptive approach, and data were collected through observation and interviews with five teachers from September to December 2023. The results showed 120 code-mixed utterances, with 30 of them being Chindolish classified based on Hoffman and Musyken's theory. The findings revealed that intra-lexical and intra-sentential code-mixing were the most frequently used types. In addition, the interviews identified that the teachers' main motivations in using code-mixing were to facilitate students' understanding, overcome language barriers, and create closeness between teachers and students. This study provides insights into multilingual practices in educational contexts in multicultural environments and their implications for language teaching.